2009
DOI: 10.1007/s11250-008-9300-9
|View full text |Cite
|
Sign up to set email alerts
|

Peste des petits ruminants virus (PPRV) infection; Its association with species, seasonal variations and geography

Abstract: The present investigation included a detailed description of the factors directly associated with PPRV infection in Pakistan. A total of 1,056 suspected serum samples were analyzed for the presence of antibodies to PPRV with no history of vaccination against PPR. The samples were collected from sixty two (62) suspected outbreaks from twenty five (25) major regions of the country. Samples were collected from the animals suffering from diarrhea and showing severe respiratory signs. Competitive enzyme linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 15 publications
12
50
5
Order By: Relevance
“…These recent findings are consistent with our earlier study (Abubakar et al, 2009) where we reported PPR on a large scale, particularly in the plains of Punjab province and also in the hilly areas (AJK, Northern areas and Northern Punjab).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These recent findings are consistent with our earlier study (Abubakar et al, 2009) where we reported PPR on a large scale, particularly in the plains of Punjab province and also in the hilly areas (AJK, Northern areas and Northern Punjab).…”
Section: Discussionsupporting
confidence: 93%
“…of Pakistan, 2008-2009). The small ruminants play an important role in sustainable agriculture and for poverty alleviation in the country.…”
Section: Introductionmentioning
confidence: 99%
“…57,59,62,65,66,67,68,70,72,74,79,80,81,84,86,87,88,89,90,93,94,95,97,98,99,105,106,109,112,113,114,116,117,118,119,120,121,125,126,128,130,131,132,133,135,137,138,139,141,142,145,147,…”
Section: Study Eligibility Form: Performance Of Diagnostic Tests For mentioning
confidence: 99%
“…The disease is characterized by high fever, necrotic stomatitis, catarrhal inflammation of the ocular and nasal mucosae, dyspnea, diarrhea and death [1]. In epidemic areas, morbidity rate has been estimated between 80-90% and mortality between 50-80% [5]. Necropsy of diseased goats revealed congested and consolidated pneumonic lungs, generalized enlargement of lymphnodes accompanied with necrosis and congestion of some lymphnodes, atrophied congested spleen and hemorrhagic gastroenteritis [6].…”
Section: Introductionmentioning
confidence: 99%